Scientific Research: An Introduction - Silva, Joao Gilberto Correa da (Scientific Research: An Introduction, 2024)
This book aims to review the foundations of the scientific approach to knowledge generation, the conceptual and methodological basis of scientific research, and the most common research methods, particularly in biology and agriculture. Science is characterized and distinguished as an approach to knowledge of nature by its objects, methods and objectives. Objects are natural phenomena; methods, disciplined cooperative research and a set of objective, systematic, rational and critical procedures that have been generically called the "scientific method"; and objective, the construction of a factual, verifiable and explanatory body of knowledge. The scientific method is the strategy of science to generate knowledge, comprising three sequential phases such as synthesis, analysis and synthesis. Its implementation is carried out by scientific research. Scientific research is employed in the three phases of the scientific method: in the initial phase of synthesis, to identify scientific problems, in the analysis phase, to try to solve these problems, and in the final synthesis phase, to incorporate the new knowledge generated into the existing body of knowledge. Thus, scientific research comprises systemic research, which focuses on global systems, in the initial and final phases, and analytical research, which focuses on subsystems, in the analysis phase. The function of the research method is to organize research procedures to minimize error, save effort, and supply an efficient collection of evidence relevant to the research objectives. The literature presents a wide range of research methods, with different procedures and names that vary according to the area of science. Due to their characteristics, each of these methods is most suitable for one of the three objectives of scientific research: exploratory, descriptive and explanatory, the latter being the objective of the synthesis phases and the first two of the analysis phase.